Pemahaman Usaha Mikro Kecil Menengah Terhadap Penerapan Peraturan Pemerintah No. 23 Tahun 2018 Tentang Penurunan Tarif Pajak Penghasilan - Hartadi, Gunawan (Jurnal Akuntansi dan Pajak, 2020)
UMKM is considered as one of primary contributors to state revenue. Due to its largest tax contributor, UMKM, the Small-Medium Enterprises (SMES), is authorised by government perceiving distinctive final income tax. Since July 1st 2018, its income tax changed from 1% of gross turnover to 0.5% owing to a regulation PP No. 23 of 2018. Therefore, this study aimed to investigate the impact of PP No. 23 of 2018 application on the SMEs' desires to expand their business. Through this regulation, the calculation of income tax for SMEs has been converted 1% of gross turnover to 0.5%. This study applied qualitative research with an expectancy theory. In this study, the interviews were conducted to three informants. As the results, this study indicated that the government regulation assisted improving the desires of SMES to escalate their businesses. Then, the SMES generally did not understand the new regulations due to lack of socialization about PP No. 23 of 2018. Moreover, the regulation was identified as an encouragement so that SMEs would not divert into online sales system. Thus, the respondents running SMEs suggested the government to synchronize both central and regional regulations so that SMEs sectors could be increased rapidly.